An Analysis of the Dynamics of Income Inequality in the Gerbangkertosusila Region - Salsavira, Nadila; Setiawati, Ririt Iriani Sri (Gorontalo Development Review, 2025)
This study aims to examine the economic and non-economic factors that influence income disparity in the Gerbangkertosusila region. Economic Growth (X1) and Open Unemployment Rate (X2) are economic indicators, while Average Years of Schooling (X3) represents the educational dimension. This research uses a quantitative descriptive method. The secondary data used are sourced from the Central Bureau of Statistics (BPS) for the period 2016 to 2023, covering seven districts/cities in the Gerbangkertosusila region. Panel data regression analysis using the Fixed Effects Model (FEM) is applied in this study. This model produces more accurate and reliable estimates by integrating the characteristics of both time series and cross-sectional data. The results show that economic growth has a negative but insignificant effect on income disparity, while the open unemployment rate has a positive and significant effect in increasing income disparity. Additionally, average years of schooling has a negative and significant effect in reducing income disparity in Gerbangkertosusila.